2023
DOI: 10.3389/fmars.2023.1134792
|View full text |Cite
|
Sign up to set email alerts
|

Decreased feeding rates of the copepod Acartia tonsa when exposed to playback harbor traffic noise

Abstract: IntroductionCopepods present the largest and most diverse group of zooplankton and their feeding behavior can affect top-down and bottom-up processes. Thus, how efficient feeding is executed determines the abundance of copepods’ prey and their predators and, with that, carbon transfer and storage in ecosystems. The rise of anthropogenic underwater noise from shipping, oil exploration and exploitation, wind farm construction and operation, and more, is increasingly changing the marine acoustic environment. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…It might be that continuous stimulation of the mechanoreceptors made D. magna less able to perceive their surroundings, resulting in lower mobility. Although we did not assess food intake, D. magna were fed ad libitum so reduced mobility probably did not result in reduced energy input, showed for copepods exposed to noise (Kühn et al, 2023), as it could be in natural populations (Read et al, 2014). Consequently, if we consider that energy input was preserved, then the energy saved from mobility might have been reallocated to tissue maintenance and reproduction, explaining the higher fitness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It might be that continuous stimulation of the mechanoreceptors made D. magna less able to perceive their surroundings, resulting in lower mobility. Although we did not assess food intake, D. magna were fed ad libitum so reduced mobility probably did not result in reduced energy input, showed for copepods exposed to noise (Kühn et al, 2023), as it could be in natural populations (Read et al, 2014). Consequently, if we consider that energy input was preserved, then the energy saved from mobility might have been reallocated to tissue maintenance and reproduction, explaining the higher fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Short-term exposures (less than four days) to air gun (intense acute noise, 150-180 dB SEL Re 1 μPa) result in the mortality of several marine species (McCauley et al, 2017) and negative effects on copepod physiology and development (Fields et al, 2019; Vereide et al, 2023). Short exposures to less intense motorboat noise (i.e., few days exposure at 126 dB RMS Re 1 μPa) do not affect the behaviour of the water flea Daphnia magna (Sabet et al, 2015, 2019; Rojas, Prosnier, et al, 2023) but decrease copepod feeding rate (Kühn et al, 2023) and rotifer fecundity (Aspirault et al, 2023). For short-lived organisms, noise exposure can easily last a substantial part of the lifespan or even exceed it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Gassie et al (1993) found that marine copepods ( Acartia fossae ) can detect water vibrations, and Buskey et al (2002) showed that vibrations can lead to acceleration in individuals of Acartia spp .. Marine zooplankton (e.g., copepods) exposed to acute airguns show a reduction of survival (McCauley et al, 2017; Fields et al, 2019; Vereide et al, 2023). Copepods also show reduced foraging rate during boat noise exposure (Kühn et al, 2023). Chaoborus flavicans larvae, an important predator of zooplankton, show more body rotations, interpreted as an anti-predatory behaviour, when exposed to boat noise for the first time (Rojas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Copepods also show reduced foraging rate during boat noise exposure (Kühn et al, 2023). Chaoborus flavicans larvae, an important predator of zooplankton, show more body rotations, interpreted as an anti-predatory behaviour, when exposed to boat noise for the first time (Rojas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%